Phosphorus and Zinc Fertilization Improve Productivity and Profitability of Rice Cultivars under Rice-Wheat System - Amanullah; Inamullah; Jawaher Alkahtani; Mohamed Soliman Elshikh; Mona S. Alwahibi; Asim Muhammad; Imran; Shah Khalid (Agronomy, 2020)
Continuous cropping of rice (Oryza sativa L.) and wheat (Triticum aestivum L.) deplete soil fertility, reduced crop productivity, and grower’s income. Phosphorus (P) and zinc (Zn) deficiencies are considered important nutritional constraints under rice-wheat cropping system. One strategy to increase crop productivity and grower’s income under the rice-wheat system is the balanced application of P and Zn fertilizers. The objective of this research was to evaluate the impact of sole and various combinations of P (0, 40, 80, and 120 kg ha−1) and Zn levels (0, 5, 10, and 15 kg ha−1) on productivity (grain yield and yield components) and profitability (net returns) of different rice genotypes (cultivars) (fine (cv.Bamati-385) vs. coarse (cv. Fakhre-e-Malakand and cv. Pukhraj)) and their residual effect on the income of the succeeding wheat crop (cv. Siran-2010). The results revealed that both rice and wheat productivity and profitability was higher with the combined application of both nutrients at higher rates (80 and 120 kg P ha−1 and 10 and 15 kg Zn ha−1). The highest productivity and profitability was obtained with the cultivation of hybrid rice “Pukhraj” (Pukhraj > Fakhre-e-Malakand > Basmati-385). It was concluded from this study that application of higher P and Zn levels and growing of hybrid rice increased productivity and profitability under the rice-wheat cropping system.